Identification and validation of the VEGF/p38MAPK/HSP27 pro-tumor inflammatory pathway: screening of active components from Patrinia villosa and evaluation of their drug-likeness - Li, Xiaochen; Ju, Yang; Yang, Xinxin; Li, Tianjiao; Wang, Shuai; Bao, Yongrui; Meng, Xiansheng (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) remains a leading cause of cancer-related mortality worldwide, with pro-tumor inflammation playing a critical role in its initiation and progression. Chronic inflammation acts as a major driving force and a distinct mechanism underlying tumorigenesis. Although previous studies have demonstrated the importance of the VEGF/p38MAPK and p38MAPK/HSP27 signaling pathways in CRC-associated inflammation, a comprehensive understanding of the entire pro-tumor inflammatory mechanism remains incomplete.MethodsThis study combined network pharmacology analysis and in vivo pharmacodynamic experiments using a p38MAPK pathway inhibitor to systematically identify and validate the VEGF/p38MAPK/HSP27 pro-tumor inflammatory signaling pathway. Western blotting was used to confirm key target proteins. Molecular docking and microscale thermophoresis (MST) experiments were conducted to screen active compounds from Patrinia villosa (PV). Molecular dynamics (MD) simulations evaluated the stability and drug-likeness of compound-target interactions.ResultsKey proteins VEGF, p38MAPK, and HSP27 were identified as critical components of the signaling pathway. Three active compounds rutin, nicotiflorin, and 4,5-dicaffeoylquinic acid (4,5-Dicqa) were found to bind these targets with high affinity. MD simulations supported the stability of these interactions and their potential as drug candidates.ConclusionThis study provides theoretical and experimental evidence for pharmacological targets involved in pro-tumor inflammation in CRC. The findings offer valuable insights for developing novel anti-inflammatory therapeutics targeting the VEGF/p38MAPK/HSP27 signaling pathway.